1983
DOI: 10.7326/0003-4819-98-2-219
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Insulin Therapy: Biochemical Effects and Clinical Repercussions

Abstract: Excessive doses of insulin cause unstable or "brittle" diabetes in many diabetic patients. Chronic insulin overtreatment can be very difficult to recognize because nocturnal hypoglycemia may be infrequent and asymptomatic. Recognition of subtle historical clues and informed interpretation of laboratory results facilitate diagnosis. Some insulin-treated diabetic patients fail to respond to severe nocturnal hypoglycemia with the acute secretion of counterregulatory hormones. "Rebound" morning hyperglycemia coinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Insulin-dependent diabetes mellitus is marked not only by a decrease in insulin levels but also by an increase in the circulating levels of the so-called counterregulatory hormones, glucocorticoids and glucagon (16,17). To evaluate whether insulin and its counter-regulatory hormones exert a direct and specific effect on liver cells, we used hepatoma cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-dependent diabetes mellitus is marked not only by a decrease in insulin levels but also by an increase in the circulating levels of the so-called counterregulatory hormones, glucocorticoids and glucagon (16,17). To evaluate whether insulin and its counter-regulatory hormones exert a direct and specific effect on liver cells, we used hepatoma cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work has shown that the plasma homocysteine level was also decreased in the streptozotocin-induced rat diabetic model with a concomitant increase in hepatic CBS enzyme activity; insulin administration reversed these effects (15). Insulin-dependent diabetes mellitus is characterized not only by insufficient circulating levels of insulin but also by elevated levels of counterregulatory hormones such as glucagon and glucocorticoids (15)(16)(17). Moreover, cyclic AMPelevating agents and glucocorticoids have been shown to increase the level of CBS enzyme activity in rat hepatoma cells (18).…”
mentioning
confidence: 99%
“…Finally, the fact that system x c − contributes to injury might seem paradoxical given its importance in the biosynthesis of the antioxidant molecule glutathione ( Watanabe and Bannai, 1987 ; Bannai et al., 1989 ; Miura et al., 1992 ; Sato et al., 1995 ; Bridges et al., 2001 ; Dun et al., 2006 ; Lewerenz et al., 2009 ). Ironically, while this pathway allows the CNS to rapidly upregulate glutathione production in response to cellular stress, we and others demonstrate its potential to exacerbate CNS pathology both in vitro and in vivo (for reviews, see Bridges et al., 2012 ; Lewerenz et al., 2013 ; Massie et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite widespread acceptance of the Somogyi phenomenon and its inclusion in standard texts on diabetes (4-7), its clinical relevance continues to be controversial (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Although individuals with IDDM frequently experience asymptomatic nocturnal hypoglycemia (18)(19)(20)(21)(22)(23), the relevance of antecedent hypoglycemia to early-morning hyperglycemia has been questioned (12,13,(15)(16)(17).…”
mentioning
confidence: 98%